Pelaksanaan Five Moment Hand Hygiene Pada Perawat Di Ruang Jimbaran: Studi Kasus - Yulianingsih; Karlina, Nonok; Najihah, Umi; Budianti, Dian (MEJORA Medical Journal Awatara, 2024)
Hand hygiene is a term for cleaning hands. The World Health Organization formulated an innovative strategy for implementing hand hygiene, namely for health workersin five moments of hand hygiene, namely before contact with patients, before carrying out nursing actions, after exposure to patient body fluids, after contact with patients, and after contact with the environment. The aim for this research is that researchers want to observe and describe the implementation of five moment hand hygiene among nurses.The number of samples in this study was 18 nurses in the Jimbaran ward at Sumber Kasih Hospital, Cirebon. Data collection carried out by researchers in managing this case study included observation,interviews and documentation studies.The research results showed that 11 respondents (61,11%) had poor implementation of five moment hand hygiene and 7 respondents (38.89%) had good implementation of five moment hand hygiene. The conclusion is that the implementation of five moment hand hygiene is not good due to the lack of knowledge and awareness of nurses about the benefits of five moment hand hygiene and the impacts caused when it is not implemented.